Developmental Prosopagnosia and Elastic Versus Static Face Recognition in an Incidental Learning Task - Bylemans, Tom; Vrancken, Leia; Verfaillie, Karl (Frontiers in Psychology, 2020)
Previous research on the beneficial effect of motion has postulated that learning a face in motion provides additional cues to recognition. Surprisingly however, few studies have examined the beneficial effect of motion in an incidental learning task and developmental prosopagnosia (DP) even though such studies could provide more valuable information about everyday face recognition compared to the perception of static faces. In the current study, eighteen young baseline controls (Experiment 1) and five DPs and ten age-matched controls (Experiment 2) participated in an incidental learning task during which both static and elastically moving unfamiliar faces were sequentially presented and were to be recognized in a delayed visual search task during which the faces could either keep their original presentation or switch (from static to elastically moving or vice versa). In the baseline group, performance in the elastic-elastic condition reached a significant improvement relative to the elastic-static condition, however no significant difference could be detected relative to the static-static condition. No significant differences were detected between conditions for both the DPs and the age-matched controls. The current study could not provide compelling evidence for a general beneficial effect of motion. Age-matched controls performed generally worse than DPs which may potentially be explained by their higher rates of false alarms. Factors that could have influenced the results are discussed.